Zinc and copper mobility experimentally disturbed oxisol and ultisol soil columns - Binadam, Aishah Ramadan Mohamed; Jusop, Shamshuddin; Che Ishak, Fauziah; Abdu, Arifin (American-Eurasian Network for Scientific Information, 2016)
The movement of heavy metals through soils amen water pollution of the metals. A study was conducted to determine (Munchong Series) and Ultisol (Bungor Series sewage sludge without plant (T2); and Soil treated with 10% sewage sludge application of sludge tended to increase th treated with10% sewage sludge contained higher Zn and Cu concentrations plant, while leachates from the planted soil contained lower Zn and Cu concentrations due to their uptake by the plants concentration of Zn in the leachates from the Ultisol it was 8.69 mg L-1 in the leachates of the Ultisol which was lower than in the soil columns after leaching proses was different among the metals, whereby zinc had lower concentration compared to th in the columns of both soils, especially for 0 which means that Zn in the soil system was more as Zn and Cu in the soils is necessary for the protection of the environment especially in tropical soils amended with sewage sludge.